PROTECTING DIGITAL DEMOCRACY: THREATS AND RESPONSES - Jennifer Irish (The Journal of Intelligence, Conflict and Warfare)
On November 18th, 2024, Ms. Jennifer Irish presented Protecting Digital Democracy: Threats and Responses for this year’s West Coast Security Conference. The presentation was followed by a question-and-answer period with questions from the audience and CASIS Vancouver executives. The key points discussed were threats to digital democracy and the core response imperatives: intervention and inoculation.